2020
DOI: 10.32598/ijt.14.2.412
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Turmeric Curcuma longa on the Body Weight and Liver Function of Japanese Quails Exposed to Dietary Aflatoxins

Abstract: Background: The contamination of poultry feed with Aflatoxins (AF) is important in terms of economic damage to the poultry industry and public health. The objective of this study was to assess the impact of Turmeric Powder (TP), containing 2.96% of Total Curcuminoids (TCM) on reducing the adverse effects of dietary AF in Japanese quails. Methods: 180 male Japanese quails aged 22-55 days were divided into six groups, and were fed basic diet (group 1, controls), or basic diet contaminated with 4 mg/kg AF and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
(54 reference statements)
2
3
0
Order By: Relevance
“…This finding confirms the results of Karimi et al. ( 2020 ), who reported that a combination of AFB 1 , AFB 2 , AFG 1 and AFG 2 in the diet significantly reduced the activity of superoxide dismutase and GPx enzymes in the liver of broiler quails. Yang et al.…”
Section: Discussionsupporting
confidence: 92%
“…This finding confirms the results of Karimi et al. ( 2020 ), who reported that a combination of AFB 1 , AFB 2 , AFG 1 and AFG 2 in the diet significantly reduced the activity of superoxide dismutase and GPx enzymes in the liver of broiler quails. Yang et al.…”
Section: Discussionsupporting
confidence: 92%
“…The results of SI agreed with Khaleghipour et al (2019) who reported that supplementing SI up to 1000mg SI/kg diets get greater BW and BWG when diet contained zero or 2.2 mg aflatoxin/kg. Improvement of BW by CR supplementation agreed with Karimi et al (2020) who reported that adding CR to quail diets (3gm and 5gm/kg diets) improved BW. Similarly, Kilany and Mahmoud (2014) reported that CR supplementation improved the final body.…”
Section: Growth Performancesupporting
confidence: 79%
“…On the contrast, the insignificant difference between zero and 250mg SI/kg diet levels agreed with Baradaran et al (2019) who reported that supplemented broiler diet with 100 mg SI /kg diet not affect significantly TAOC. Karimi et al (2020) reported that the addition of CR in quail diets improved antioxidant status. Kilany and Mahmoud (2014) reported that CR supplementation caused a significant decrease in MDA, on the other hand, it cause significant increase in GSH-Px.…”
Section: Antioxidant Status and Aflatoxin In Liver And Musclementioning
confidence: 99%
See 1 more Smart Citation
“…The severity of liver histological pathologies including periportal fibrosis, hyperemia, and leukocyte infiltration were reduced in the treated group. 137 In cerium chloride (CeCl 3 , i.p. )-induced mouse brain injury, C. longa (100 mg/kg, p.o.…”
Section: Antioxidant Effects Of C Longa Animal Studiesmentioning
confidence: 99%